2004
DOI: 10.1021/bi0496438
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Conformational Changes and Topology of a Herpesvirus Translocating Peptide in a Membrane-Mimetic Environment

Abstract: Pol peptide, an oligopeptide corresponding to the 27 C-terminal amino acids of DNA polymerase from herpes simplex virus type 1, has recently been suggested to translocate from endosomal compartments into the cytosol after being intracellularly delivered via a protein carrier. While an acidic environment was thought to be important for Pol peptide membrane translocation, the mechanism of translocation remains unclear. To investigate the influence of an acidic environment on the conformational properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…[22][23][24][25] Like exchangeable apolipoproteins, the synuclein sequences are characterized by the presence of a set of imperfect 11-residue repeats. On the basis of this 11-mer periodicity, Segrest et al have suggested the possibility that apolipoprotein A-I forms an 11/3 helix with a pitch of 3 turns per 11 residues.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Like exchangeable apolipoproteins, the synuclein sequences are characterized by the presence of a set of imperfect 11-residue repeats. On the basis of this 11-mer periodicity, Segrest et al have suggested the possibility that apolipoprotein A-I forms an 11/3 helix with a pitch of 3 turns per 11 residues.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the failure of these compounds to act as neutral sPRE probes, they are nonetheless thought to be useful as a coarse tool to map local electrostatic fields of proteins by NMR spectroscopy 26. Aminoxyl radicals attached to lipophilic anchors have also been developed to monitor amphipathic peptides and membrane proteins in lipid micelle environments 17b,c. 27…”
Section: Spre Probesmentioning
confidence: 99%
“…Mechanistically, this can be done by ligand recognition, protein conformational changes, or posttranslational modifications (PTMs). [1][2][3][4][5] PTMs are especially important in the molecular communication across cellular processes, including signal transduction and the host response to viral infection. [6][7][8][9][10][11][12][13] Viruses must utilize this form of cellular communication for their own nefarious purposes.…”
Section: Introductionmentioning
confidence: 99%